STRENGTHENING CHARACTER EDUCATION IN STUDENT DISCIPLINE THROUGH AQIDAH AKHLAK LEARNING AT MTS. DARUSSALAM BOGOR CITY - Toyyibudin, Toyyibudin; Zulfiqri, Muammar (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Character building, particularly discipline, has become a primary focus in Indonesia's national education system, reinforced by Presidential Regulation No. 87 of 2017 on the Strengthening of Character Education (PPK). This has become increasingly urgent given the rising cases of juvenile delinquency such as brawls, bullying, drug abuse, and other undisciplined behaviors, with KPAI data showing a 1.1% increase in brawls in 2018, and 24-28% of drug abusers being students according to the BNN in 2019. In this context, the learning of Aqidah Akhlak (Islamic Creed and Ethics) in madrasahs, as implemented in MTs. Darussalam Kota Bogor, plays a strategic role in shaping the character and discipline of students, although its implementation still faces various challenges that require synergy between schools, families, and the community to optimize the formation of disciplined student character in accordance with Islamic values and national education demands. Descriptive statistical analysis shows that the level of strengthening disciplinary character education in Aqidah Akhlak learning tends to be in the moderate category with an average value of 66.51 and relatively evenly distributed data. However, previous research indicates that the strengthening of disciplinary character education can reach a high category when supported by factors such as teacher competence, learning facilities, and parental involvement. Meanwhile, descriptive statistical analysis of student discipline shows a tendency towards high and relatively homogeneous levels of discipline. Furthermore, the results of Pearson correlation analysis reveal a significant positive relationship between the strengthening of character education and student discipline, although some previous studies have found different results, indicating that external factors such as family environment and social interactions also play an important role in shaping student discipline. At MTs. Darussalam Kota Bogor, there are several special programs designed to strengthen character education, including: 1. Friday Blessing Program, 2. Dhuha Program, 3. Dzikir Asmaul Husna and Shalawat Nariyah, 4. Extracurricular Activities. The learning of Aqidah Akhlak at MTs. Darussalam Kota Bogor has a very significant implication in shaping the younger generation to be people of integrity, ethics, and responsibility. Although this approach has shown positive results in the formation of student character and discipline, there are still several challenges that need to be addressed, such as the tendency towards cognitive-based learning, formal routines without deep meaning, and the influence of external factors such as social media and social environments. To achieve optimal and sustainable results in the formation of student character and discipline, a synergistic effort between schools, families, and the community is required to support this process.